PENGARUH PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEGAWAI KANTOR DISTRIK NAVIGASI KELAS I PALEMBANG DIREKTORAT JENDERAL PERHUBUNGAN LAUT KEMENTERIAN PERHUBUNGAN - Amriyadi Amriyadi; Luis Marnisah; Fakhry Zamzam (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2020)
The purpose of this study was to obtain a detailed description of the effect of occupational safety and health of employees at the Palembang Class I Navigation District Office of the Directorate General of Sea Transportation, Ministry of Transportation, with quantitative analysis, using SPSS statistical tools, 20 using quantitative descriptive methods, the number of respondents 44 employees at the locus. research. The results showed that partially occupational safety and occupational health variables had a positive and significant effect, and simultaneously the effect of work safety and occupational health together had an effect on employee performance, but partially occupational health was more dominant in influencing employee performance. It is suggested that in order to achieve good performance related to K3, then the health factor is prioritized, then work safety